Time-reversal symmetry in optics - Leuchs, Gerd; Sondermann, Markus (Physica Scripta, 2012)
The utilization of time-reversal symmetry in designing and implementing (quantum) optical experiments has become more and more frequent over the last few years. We review the basic idea underlying time-reversal methods, illustrate it with several examples and discuss a number of implications. © 2012 The Royal Swedish Academy of Sciences.